Visual Audio Based Media Development for Speaking Skills on Thank You Conveying Material and A Request for Help for Grade I Elementary School Students - Nurfitriana, Dini; Sudin, Ali; Djuanda, Dadan (Jurnal Pena Ilmiah, 2021)
This research was conducted as a way to help overcome problems regarding students' difficulties in understanding the material and how to express good gratitude and requests for help related to speaking skills in grade I at SDN Sindang I. The instruments used are in the form of interview guidelines and validation sheets. Initial data collection techniques using interviews. Methods used research and development methods(Design and Development)using qualitative approaches. The results showed that validation of audio visual-based media development by material experts in round I by 74% and round II by 88%. While the results of validation by media design experts and users (teachers) are carried out one round and obtained a rating of 88% from media design experts and 91.58% from users (teachers). This shows that audio visual-based media belongs to a very valid category and can be used without revision based on conversion of validity assessment criteria.